HUBUNGAN ANTARA MOTIVASI BELAJAR DAN HASIL BELAJAR SISWA SD DALAM PEMBELAJARAN IPA - Iman Hadi Sunarya, Encep; Dahlani, Awaliyah; Santika Yuliandini, Elvira; Hadjar Fajriah, Rini (LPPM UNSAP & Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Learning motivation has a close relationship with students' academic learning outcomes in science subjects in elementary schools. Learning motivation is a drive that comes from within students and from their surrounding environment that encourages them to learn. This study uses a literature study method to examine the relationship between learning motivation and learning outcomes in the form of student academic achievement in science subjects in elementary schools. The results of the study show that high learning motivation will encourage students to try to overcome challenges and make students not give up easily when facing difficulties in learning science. Students who have high learning motivation will be more enthusiastic in learning activities and doing science assignments, both in the form of assignments given by teachers at school and assignments in the form of homework. Active involvement in the learning process will have a positive impact on obtaining optimal learning outcomes in science subjects in elementary schools.